Impact of lifestyle modification on glycemic control and cognitive function among Type II diabetes mellitus patients - Iman I Salama; Samia M Sami; Somaia I Salama; Ghada A Abdel-Latif; Ahmed Aboulghate; Hala M Raslan; Amira Mohsen; Hanaa Rasmy; Mona Hamed Ibrahim; Mona MF Ganem; Aida M Abdelmohsen; Lobna A El-Etreby; et al. (Future Science OA)
Aim: Assessing impact of lifestyle modification on Type 2 diabetes mellitus (T2DM) glycemic control and cognitive function. Subjects & methods: Prospective study was conducted on T2DM patients (92 patients as interventional group and 92 patients conventional therapy). Results: After 6 months, significant improvements of HbA1c, oxidant and antioxidant, lipid profile, and cognitive function among only the interventional group (p < 0.05). Using logistic analysis, conventional therapy, DM duration >10 years, lower education, HbA1c baseline >7 were significant predictive risks for uncontrolled DM (AOR 4.2, 2.9, 2.7 and 2.2, respectively). While, conventional therapy, baseline mild cognitive impairment (MCI) and females were significant risks for MCI (AOR 11.5, 10.8 and 4.8, respectively). Conclusion: Lifestyle modification is a very important for glycemic control and cognitive function. Clinical Trial Registration: NCT04891887 (ClinicalTrials.gov)